Evolution in the Enabling Factors for Transformational Change in Forestry and Land Use Policy Processes: The Case Of Redd+ in Cameroon. (1st March 2019) - Chia, E.L.; Hubert, D.; Carodenuto, S.; Sene, O.
To mitigate climate change through forestry and land use, countries are expected to shift away from policies and practices that drive deforestation to ones that reduce forest loss. This paper draws on political economy concepts to assess the evolution in the enabling measures for transformational change in forestry and land use policy processes in Cameroon. The findings indicate that actors have diverse stances on the capacity of existing policy measures to guarantee transformational change. The policy environment has evolved with proposals on institutional arrangements and policy reforms that are far from concrete reforms as expected. There is significant room for fine-tuning proposed policy and institutional reforms to enable Cameroon respond to its international emission reduction commitments. For example, putting forward clear-cut incentive and regulatory mechanisms; enhance and create new anti-deforestation coalitions; generate concrete specific/tailored sector ideas and information; and enhance negotiations between sectoral interests. However, these can only be achieved in the long-term with continuous support.